Examining the Rate of the Yolk Uptake Through the Yolk Stalk in the Post-hatch Broiler Chick By Using Cr 51 Labelled Microspheres as A Tracer - Abrani Sulaiman (Bioscientiae, 2006)
The trial was conducted with the purpose to investigate the usefulness 51Cr labeled microspheres as tracers in yolk absorption and or its rate absorption through yolk stalk.  In the trial,  20 broiler chicks were injected in the yolk sac on Day 0 with with 0.2 ml of radioactive 51Cr labelled microspheres suspended in physiological saline. Injection was made with directly through the abdominal wall into the underlying yolk sac. At 1300 h each day for five days, four chicks were sacrificed at random by cervical dislocation. For each chick, total body  weight, and the weight and level of radiation (cpm) from the following organs were determined: total body, carcass, intestine, liver,  yolk sac, gizzard, kidney, and excreta. The level of radiation from tissues were obtained with the use of a High Energy Gamma Scintillator Probe containing NaI crystal. Results show body weight, and relative intestine, and excreta weight increased between 1 and 5 days; conversely, relative yolk sac weight decreased between 1 and 5 days.  Relative yolk stalk weight peaked on Day 4, but was not significantly different from that at Day 1. Relative cpm of the liver, yolk sac, yolk stalk, and excreta were influenced by day of age. The level of radiation was significantly higher in the yolk sac, kidney, and excreta than in the carcass, intestine, liver, blood, and gizzard. It was concluded that significant amounts of yolk may be absorbed and pass through the yolk stalk into the intestine through 5 days of age in post-hatch chicks and the rate of movement increases through 5 days post-hatch, particularly after Day 3.